2004
DOI: 10.1523/jneurosci.3302-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Platelet-Derived Growth Factor-Responsive Precursor from the Embryonic Ventral Forebrain

Abstract: Oligodendrocyte progenitor cells express platelet-derived growth factor (PDGF) receptor-␣ and, when expanded in PDGF only, have been shown to generate oligodendrocytes and astrocytes but never neurons. Recent evidence suggests that oligodendrocytes are generated by a common progenitor that also generates neurons but not astrocytes. We used the neurosphere culture system to isolate embryonic ventral forebrain, PDGF-responsive precursors (PRPs). We report that the medial ganglionic eminence is the source of PRP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 57 publications
6
68
0
Order By: Relevance
“…However, when we isolated cells from the injury site by NG2 or PDGFR␣ surface staining (SI Fig. 6 B and C), no multipotent neurospheres were obtained (0 of 35,000 and 25,000, respectively), even upon addition of PDGF to these cultures (26). These data therefore support the idea that mature astrocytes have a rather unique capacity to dedifferentiate and resume multipotency, in keeping with their developmental origin (27).…”
Section: Fate Mapping Of Quiescent Astrocytes Upon Sw Injury By Lymphsupporting
confidence: 53%
See 1 more Smart Citation
“…However, when we isolated cells from the injury site by NG2 or PDGFR␣ surface staining (SI Fig. 6 B and C), no multipotent neurospheres were obtained (0 of 35,000 and 25,000, respectively), even upon addition of PDGF to these cultures (26). These data therefore support the idea that mature astrocytes have a rather unique capacity to dedifferentiate and resume multipotency, in keeping with their developmental origin (27).…”
Section: Fate Mapping Of Quiescent Astrocytes Upon Sw Injury By Lymphsupporting
confidence: 53%
“…From hGFAP-eGFP mice, cells expressing NG2 or PDGFR␣ were isolated from either the GFP ϩ or GFP Ϫ cells and were tested for neurosphere formation according to ref. 45 or in the presence of PDGF (26).…”
Section: Lentiviral Vector Productionmentioning
confidence: 99%
“…To test whether PRL can act on OPCs in the white matter of the adult CNS to increase their proliferation and generation of oligodendrocytes, we isolated PDGF-responsive OPCs in vitro as neurospheres (Chojnacki and Weiss, 2004). The CC of adult virgin females was dissociated and cultured in the presence of PDGF for 10 -12 d in vitro, resulting in the formation of adult OPC neurospheres (Fig.…”
Section: Prl Signaling Regulates Pregnancy-induced Opc Proliferationmentioning
confidence: 99%
“…Termed oligodendrocyte progenitor cells (OPCs) and PDGF-responsive neural precursors (PRPs) (Chojnacki and Weiss, 2004), they are slowly dividing and primarily generate oligodendrocytes (ffrenchConstant and Raff, 1986;Wolswijk and Noble, 1989;Gregg et al, 2007). OPCs/PRPs and adult periventricular NSCs are also thought to be two distinct neural precursor populations.…”
Section: Introductionmentioning
confidence: 99%
“…It was later shown that GFAP-expressing NSCs activated by the cytosine arabinoside-induced death of their progeny, the transit-amplifying progenitors, express the EGF receptor (EGFR) (Pastrana et al, 2009). Furthermore, EGFR and PDGFR␣ label distinct neural precursor populations during embryonic development (Chojnacki and Weiss, 2004) and in the adult periventricular area (Jackson et al, 2006). However, postnatal and adult OPCs/PRPs have now been reported to express EGFR (Aguirre et al, 2004).…”
Section: Introductionmentioning
confidence: 99%